2017
DOI: 10.1016/j.healthpol.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Trade policy governance: What health policymakers and advocates need to know

Abstract: Trade policies affect determinants of health as well as the options and resources available to health policymakers. There is therefore a need for health policymakers and related stakeholders in all contexts to understand and connect with the trade policymaking process. This paper uses the TAPIC (transparency, accountability, participation, integrity, capacity) governance framework to analyze how trade policy is commonly governed. I conclude that the health sector is likely to benefit when transparency in trade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 7 publications
0
30
0
Order By: Relevance
“…Nutrition and climate change actors have reported constraints on their ability to engage in the policy development processes with trade policymakers. Barriers identified at the national level include limited opportunities for consultation and input, lack of transparency around trade agreement negotiations, and a broader lack of public deliberation about the social, environmental and health impacts of trade agreements 61,67,76 .…”
Section: The Political Economy Of Tradementioning
confidence: 99%
“…Nutrition and climate change actors have reported constraints on their ability to engage in the policy development processes with trade policymakers. Barriers identified at the national level include limited opportunities for consultation and input, lack of transparency around trade agreement negotiations, and a broader lack of public deliberation about the social, environmental and health impacts of trade agreements 61,67,76 .…”
Section: The Political Economy Of Tradementioning
confidence: 99%
“…The analysis suggests that institutional changes are urgently needed to formally include health representation, and echoes calls for greater transparency, accountability, participation, integrity and capacity in the governance of trade policy. 17 Thailand has been a leader in this regard with its interdepartmental International Trade and Health Programme to generate evidence-based analyses of the potential health impacts of trade negotiations for government. 37 Thailand's former Constitution included requirements for parliamentary approval of trade negotiation frameworks but these constitutional protections were unfortunately after the 2014 coup d' état.…”
Section: Discussionmentioning
confidence: 99%
“…Key trade governance challenges noted in the literature include issues of transparency, accountability, participation, integrity and capacity. 17 Analysis of framing in trade policy has highlighted the power of a dominant neoliberal market-oriented discourse that privileges exporter interests and market liberalisation. 18 This dominant framing aligns with the interests of exporters including multinational pharmaceutical companies and ultraprocessed food and alcohol exporters.…”
Section: Key Messagesmentioning
confidence: 99%
“…For example, it may lead to potential de-skilling [ 9 ] and render them vulnerable to the global economic crisis [ 3 , 10 ]. Previous studies have indicated an insufficient involvement of health professionals in trade negotiations relating to public health [ 8 , 11 ]; this may adversely impact nurses and healthcare institutions. Therefore, it is important to analyze the provision of bilateral agreements from the perspective of the healthcare industry.…”
Section: Introductionmentioning
confidence: 99%